Effect of concentrations and characterization of nickel oxide thin films prepared by SILAR method. (2022) - Nachammai, J.; Perumal, P.; Deivamani, D.; Saravanakumar, S.
Highlights: Very easy and simple SILAR technique has been used in our laboratory to prepared NiO thin films. There is no requirement of expensive and sophisticated instruments for the preparation method. Low operating temperature, thickness and growth rate of the nano films can be easily controlled by varying the deposition cycles and other preparative parameters. Good quality NiO nano films successfully deposited onto glass substrate using the low cost and effective SILAR method. The as prepared nano films analysed and suggested for opto-electronic applications. Abstract: NiO thin films were synthesized by Successive Ionic Layer Adsorption and Reaction method (SILAR). The structural, morphological, optical properties of the as prepared films were characterized by X-ray Diffraction, U-V visible spectroscopy, Photoluminescence, Scanning Electron microscopy, Energy dispersive X-ray spectrum. The XRD results confirms the presence of high purity, polycrystalline face centered cubic crystal with orientations along different planes. The optical transmittance of the different concentrations of the NiO thin films were between 60% and 90%. PL peaks were observed in 380 nm and 520 nm. Elemental composition confirms the presence of Ni and O elements in NiO thin films. The surface morphology studies revealed that the prepared films are homogeneous, smooth and well adherent.